Analisis Adverse Drug Reactions pada Pasien Asma di suatu Rumah Sakit, Surabaya - Lorensia, Amelia; Canggih, Beny; Wijaya, Rizka Indra (Jurnal Farmasi Indonesia, 2013)
Asthma is a chronic inflammatory disease of the respiratory tract. Treatment of asthma can lead to ADRs (adverse drug reactions), which can aggravate asthma symptoms. The purpose of this study was to analyze the incidence of ADRs in patients with asthma. The study design is divided into retrospective studies, for hospitalized patients and cross-sectional with purposive sampling to outpatient. Any actual ADRs that ocured was calculated using the Naranjo probability scale. The number of hospitalized patients were 60 people and outpatients were 22 people. The number of ADRs that occur were 39 cases, consisted of 36 cases of ADRs in Â hospitalized patients with asthma and 3 cases of ADRs in outpatient asthma patients. Drug groups most involved in ADRs was B2-agonist group. Naranjo scale calculations on ADRs that occured that the possibility of ADRs. The most common ADRs are in asthma therapy, so it takes the role of pharmacists in monitoring ADRs in asthma treatment to prevent and minimize the occurrence of ADRs.Keywords : asthma, naranjo scale, hospitalized patient, outpatient.